Adolescents and young adults' (AYA) views on their cancer knowledge prior to diagnosis: Findings from a qualitative study involving AYA receiving cancer care - Ruth I. Hart; Fiona J. Cowie; Angela B. Jesudason; Julia Lawton (Wiley, 2021)
Abstract Background Cancer is rare amongst adolescents and young adults (AYA). Previous research has reported (healthy) AYA's knowledge of risk factors and symptoms as limited, with this potentially leading to delays in help‐seeking and diagnosis. Objectives We explored AYA's views on their cancer knowledge prior to diagnosis and if/how they perceived this as having affected their experiences of diagnosis and care. Methods We interviewed 18 AYA diagnosed with cancer (aged 16‐24 years). Interviews were recorded and transcribed verbatim. We undertook qualitative descriptive analysis, exploring both a priori topics and emergent themes, including cancer knowledge prior to diagnosis. Results Adolescents and young adults characterized their knowledge of cancer and treatment prior to diagnosis and treatment initiation as limited and superficial. AYA perceived gaps in their knowledge as having profound consequences throughout their cancer journey. These included: hindering recognition of symptoms, thereby delaying help‐seeking; impeding understanding of the significance of tests and referrals; amplifying uncertainty on diagnosis; and affording poor preparation for the harsh realities of treatment. Conclusions Adolescents and young adults perceived their limited cancer knowledge prior to diagnosis as affecting experiences of diagnosis and initial/front‐line care. These findings prompt consideration of whether, when and how, AYA's knowledge of cancer might be improved. Two broad approaches are discussed: universal education on AYA cancer and/or health; and targeted education (enhanced information and counselling) at and after diagnosis. Patient or Public Contribution Our work was informed throughout by discussions with an advisory group, whose membership included AYA treated for cancer.